ANALYSIS OF NAIK DANGO TRADITION VALUES IN THE DAYAK KANAYATN ETHNICITY IN BANDANG HAMLET - Helana, Helena; Bahari, Yohanes; Ismiyani, Nining; Haqjo, Sharafatullah (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
This study aims to examine the traditional values of the rising Dango among the Dayak Kanayatn in Bandang Hamlet, Keranji Paidang Village, Sengah Temila District, Landak Regency. The method in this research is the descriptive qualitative method. Data collection techniques in this study are observation, interviews and documentation. The data analysis techniques used are data presentation, data reduction and drawing conclusions. In this study, the researchers used 3 informants. The results showed that the Naik Dango tradition which is carried out once a year is a form of thanksgiving for the rice harvest carried out by members of the Dayak Kanayatn ethnic community, especially in the Dusun Bandang area, Keranji Paidang Village, Sengah Temila District, Landak Regency. What was done by the people in Bandang Hamlet during the Naik Dango Tradition was the procession which was carried out when performing the Naik Dango ritual. The procession in it is the initial procession, the core procession and the final procession. Apart from that, there are also value functions in the Naik Dango tradition, namely guidelines for successful rice harvests, social control and solidarity. There is also meaning in the tradition of rising the dango, namely cultural, educational and religious aspect.